2017
DOI: 10.3389/fphar.2017.00175
|View full text |Cite
|
Sign up to set email alerts
|

Phellinus linteus Mycelium Alleviates Myocardial Ischemia-Reperfusion Injury through Autophagic Regulation

Abstract: The incidence of myocardial ischemia-reperfusion (IR) injury is rapidly increasing around the world and this disease is a major contributor to global morbidity and mortality. It is known that regulation of programmed cell death including apoptosis and autophagy reduces the impact of myocardial IR injury. In this study, the cardioprotective effects and underlying mechanisms of Phellinus linteus (Berk. and Curt.) Teng, Hymenochaetaceae (PL), a type of medicinal mushroom, were examined in rats subjected to myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Phellinus linteus mycelium (PLM), a well-known medicinal mushroom, has been used in Asian countries for many centuries to prevent or treat diseases such as gastroenteric dysfunction, hemorrhage, diarrhea, rheumatoid arthritis, and cancers [ 48 ]. Our findings revealed that PLM inhibited inflammatory responses in MIA-induced osteoarthritis rats.…”
Section: Discussionmentioning
confidence: 99%
“…Phellinus linteus mycelium (PLM), a well-known medicinal mushroom, has been used in Asian countries for many centuries to prevent or treat diseases such as gastroenteric dysfunction, hemorrhage, diarrhea, rheumatoid arthritis, and cancers [ 48 ]. Our findings revealed that PLM inhibited inflammatory responses in MIA-induced osteoarthritis rats.…”
Section: Discussionmentioning
confidence: 99%
“…There was a study that reported that the left main coronary artery of rats was ligated for 1 h and then reperfused for 3 h. Administrating of phellinus linteus mycelium could alleviate myocardial damage through autophagic regulation, which the accompanying evidence was that caspase-3 and caspase-9 activation decreased, Bcl-2/Bax ratio increased, AMPK phosphorylation elevated, and Beclin-1 and p62 levels decreased. This study emphasized the enhancement of protective autophagy and inhibition of excessive autophagy to achieve autophagy balance [ 35 ]. The articles of this section are summarized in Table 1 .…”
Section: Potential Effect Of Autophagy In the Treatment Of Myocardmentioning
confidence: 99%
“…Beclin1 and microtubule-associated proteins 1A/1B light chain 3B (LC3β) are key proteins regulating both autophagy and cell death. Moreover, sequestosome-1 (SQSTM1/p62) is a protein targeting the specific cargo of autophagy [ 17 ]. Beclin1 can also interact with the anti-apoptotic protein BCL2, where its binding state plays a key part in coordinating the cellular decision to undergo autophagy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%